Gestión del riesgo de desastres: Competencias para una nueva cultura hidroambiental - Charpentier, Claudia (2022)
The study was aimed to develop and validate competencies, methodologies, and teaching resources for a new hydro-environmental culture in disaster risk management for Costa Rican students and teachers of the second cycle of the Cahuita Excelencia Elementary School in Limón. The research was developed under an interpretive and propositional qualitative approach with the participation of nine national and international experts (3 in Disaster Risk Management [Group 1], 3 in Climate Change [Group 2], and 3 in Education [Group 3]), using the Delphi method which consisted of 3 phases: preparation, consultation, and consensus. Results indicate that Groups 1 and 2 developed 43 competencies, of which ten were validated by each group. Group 1 distributed competencies into conceptual, internal, and external, while Group 2 only distributed cognitive competencies, both for children and teachers, taking into account indicators, didactic resources, and methodologies. During Phase 3, Group 3 adjusted and validated the competencies developed by Groups 1 and 2, which consist of 20 competencies and a series of resources and methodologies. It is concluded that competencies will contribute to guarantee better preparation for vulnerability and risk events caused by climate change. The reference educational material could be adjusted to other regions of Costa Rica and Latin America.